DEVELOPMENT OF ELECTRONIC GOVERNMENT AS A DRIVER OF COMPETITIVENESS OF EUROPEAN UNION COUNTRIES - Svitlana Rybkina; Elmira Sokolova (Публічне управління та регіональний розвиток)
Digital technologies in public administration are a key driver of change in modern society. They contribute to increasing transparency, accessibility of public services and efficiency of interaction between authorities and citizens. The implementation of e-government opens up new opportunities for innovation in the field of public administration and communications. Among the main tools of digitalization, it is worth noting electronic identification (eID), automated data registers and online platforms that simplify the interaction of citizens with authorities, reducing time costs and creating a transparent environment. These digital solutions not only reduce administrative barriers, but also form the basis for building trust between the public and government structures. They allow for the effective implementation of socially significant projects and contribute to sustainable development by improving access to information and services. The growing role of technology in the interaction of the state with the public sector is an important tool for ensuring the well-being of citizens, contributing to socio-economic progress and strengthening institutions. Digitalization in the context of today's global challenges is a crucial factor for creating inclusive and effective governance.